The connection between prospective teachers’ procedural and conceptual knowledge with problem-posing skills of fractions - Yesi Martha Afrillia; Zetra Hainul Putra; Eddy Noviana; Riyan Hidayat; Dahnilsyah Dahnilsyah (Institute of Advanced Engineering and Science, 2022)
This study examined the connections between procedural and conceptual knowledge of addition and subtraction of fractions with the problem-posing skills of prospective primary teachers. The applied method was a correlational study with structural equation modeling-partial least square (SEM-PLS) analysis. The sample in this research was 101 third-year students from a primary teacher education study program of a public university in Riau, Indonesia. The results showed that prospective primary teachers have high procedural knowledge and problem-posing skills on addition and subtraction. However, they have poor performance on problems related to conceptual knowledge of addition and subtraction of fractions. Then, the results also revealed a significant connection between procedural and conceptual knowledge with problem-posing skills on addition and subtraction of fractions of prospective primary teachers. Improving prospective primary teachers’ procedural and conceptual knowledge could raise their problem-posing skills on adding and subtracting fractions.